Optimization of Process Parameters of Immobilized Escherichia Coli for Cyclodextrin Production - Nur Nadia, Mohd Zakaria; Rohaida, Che Man; Siti Zubaidah, Sulaiman; Siti Kholijah, Abdul Mudalip; Nor Hasmaliana, Abdul Manas; Navika Yamani, Laura (Semarak Ilmu Publishing, 2023)
The growing interest toward cylclodectrin (CD) application in industries is due to its unique structure that able to form inclusion complexes with substances. However, the problems arise during the CD synthesis using the commercial enzyme (cyclodextrin glucanotransferase) are low production rate and the process is expensive. Hence, cell immobilization system was used. The objective of this study is to optimize the process parameters using Response Surface Methodology to increase the CD production of the immobilized cell. High CD production was achieved after the optimization process. The reusability of immobilized cell also can be reuse up to six cycles using the optimized parameters. The findings propose that optimization process increased the CD production and made it more valuable for industrial application.